Engineering considerations in commercial watermarking. - Decker, S. (IEEE Communications magazine)
This article explores some of the engineering and design considerations for a commercial implementation of watermarking technology. Watermarking technology has many performance characteristics that rival one another in the system design space. After a discussion of these characteristics, we examine the engineering trade-offs required for a particular commercial instantiation of watermarking technology, the Digimarc Media Bridge system. We begin with an overview of the system and its requirements, and then discuss the engineering considerations that led to its successful implementation